Phosphorylation alters Bim‐mediated Mcl‐1 stabilization and priming - Conage‐Pough, Jason E.; Boise, Lawrence H. (The FEBS journal, 2018)
Mcl‐1 is a highly labile protein, subject to extensive post‐translational regulation. This distinguishes Mcl‐1 from other antiapoptotic proteins and necessitates further study to better understand how interactions with proapoptotic Bcl‐2 proteins affect its regulation. One such protein, Bim, is known to stabilize Mcl‐1, and Bim phosphorylation has been associated with increased Mcl‐1 binding. Consequently, we investigated the potential impact of Bim phosphorylation on Mcl‐1 stability. We found that Bim stabilizes and primes Mcl‐1 in RPCI‐WM1 cells and is constitutively phosphorylated. Additionally, introduction of several phospho‐mimetic and unphosphosphorylateable Bim mutations resulted in altered Mcl‐1 stability and distinct Bim binding to antiapoptotic proteins. These findings suggest Bim phosphorylation not only regulates Mcl‐1 stability but also is a potential mechanism for enforcing Mcl‐1 dependence. Mcl‐1 is highly labile and frequently targeted for ubiquitination. Wild‐type Bim overexpression stabilized and preferentially primed Mcl‐1. Conversely, the introduction of several Bim phosphorylation site mutations resulted in the altered ability to stabilize Mcl‐1 and differential Bim binding to antiapoptotic proteins. Our findings suggest Bim phosphorylation influences Bcl‐2 family priming and dependence.